2015
DOI: 10.1080/21645515.2015.1101198
|View full text |Cite
|
Sign up to set email alerts
|

A postmarket safety comparison of 2 vaccination strategies for measles, mumps, rubella and varicella in Italy

Abstract: It is strategically important to monitor the safety profile of vaccination schedules in order to achieve and maintain high levels of coverage. We analyzed the cohort of individuals actively invited for measles, mumps, rubella and varicella (MMRV) vaccination in the Veneto region (north-east Italy) from 8/1/2013 to 7/31/2014, assessing the onset of adverse events (AE) relating to 2 different vaccination strategies for MMRV (MMR+V vs MMRV). During the vaccination session at 14 months old, parents were given a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Data of our study were consistent to literature findings. In a recent study published by Cocchio et al [44], fever was the most common systemic reaction after the MMRV vaccine, and the incidence of febrile seizure was 0.2%. Also, this study was based on active surveillance (then, the reporting rate was expected as higher) but causality assessment was not carried out, therefore we cannot evaluate the link between the vaccine and AEFIs [44,45].…”
Section: Discussionmentioning
confidence: 93%
“…Data of our study were consistent to literature findings. In a recent study published by Cocchio et al [44], fever was the most common systemic reaction after the MMRV vaccine, and the incidence of febrile seizure was 0.2%. Also, this study was based on active surveillance (then, the reporting rate was expected as higher) but causality assessment was not carried out, therefore we cannot evaluate the link between the vaccine and AEFIs [44,45].…”
Section: Discussionmentioning
confidence: 93%
“…This study was based on active surveillance (than, the reporting rate was expected as higher) but causality assessment was not carried out, than we cannot evaluate the link between vaccine and AEFIs. 44 In a 2014 study on 3112 children, 10 febrile seizures were reported following MMRV administered alone or with other vaccines (rate: 3.21 × 1000 doses). Three of the seizures were reported by the investigator as related to vaccination (rate 1/ 1000 doses) and seven were reported as probably or definitely not related to vaccination: also, in this case, the authors did not use the WHO algorithm and it makes difficult to compare the results.…”
Section: Discussionmentioning
confidence: 99%
“…GMTs are shown above the population columns. P-value of the GMT between the first (1-11) and second(12)(13)(14) group is <0.05.…”
mentioning
confidence: 86%
“…Since then, the attenuated varicella strain has been included in the formulation of the vaccine. This can be administered at the same session as trivalent anti-measles-mumps-rubella plus the monovalent anti-varicella vaccine or as quadrivalent MMRV combined vaccine [14].…”
Section: Introductionmentioning
confidence: 99%